If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 5y + -3x + -2y = 0 Reorder the terms: -1x + -3x + 5y + -2y = 0 Combine like terms: -1x + -3x = -4x -4x + 5y + -2y = 0 Combine like terms: 5y + -2y = 3y -4x + 3y = 0 Solving -4x + 3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. -4x + 3y + -3y = 0 + -3y Combine like terms: 3y + -3y = 0 -4x + 0 = 0 + -3y -4x = 0 + -3y Remove the zero: -4x = -3y Divide each side by '-4'. x = 0.75y Simplifying x = 0.75y
| 4(5y+7z)-28z= | | 5/13+6/11 | | 2(6y+2z)-4z= | | k+-9k-8k-10k=-20 | | 5y(2y-4)+14y= | | 9a-3(a+3)= | | 8c-10c-6=10 | | -1a-24=5a | | 2x+7(8+2x)=8 | | 6(4y+5z)-30z= | | 4log(x-6)=11 | | 16h-13h-2h-1=15 | | (25.12^2)/4(3.14) | | 52=12+4w | | -7/9(x-y+36) | | 2c-c=14 | | (80x-54y)-(62x+9y)= | | 8y-y+2y=18 | | 5(2y+4z)-20z= | | 15+3y=25 | | 4x-5/3x | | 6y(3y-4)+22y= | | (11x+23y)+(38x+50y)= | | -(2x^2-7x+7)= | | 4y(3y-6)+19y= | | A=8*(3.14) | | 4x-6=4(x+5) | | (63x+45y)-(13x+40y)= | | 6(x-6)+20=2(x-6) | | -(12b-10)+5(3b-2)= | | 8x+3=-3+3x+21 | | (23x+64y)+(33x-16y)= |